A core outcome set for the treatment of pregnant women with pregestational diabetes: an international consensus study. (3rd August 2021) - Kgosidialwa, O; Bogdanet, D; Egan, AM; O'Shea, PM; Newman, C; Griffin, TP; McDonagh, C; O'Shea, C; Carmody, L; Cooray, SD; Anastasiou, E; Wender‐Ozegowska, E; et al.
Abstract : Objective: To develop a core outcome set (COS) for randomised controlled trials (RCTs) evaluating the effectiveness of interventions for the treatment of pregnant women with pregestational diabetes mellitus (PGDM). Design: A consensus developmental study. Setting: International. Population: Two hundred and five stakeholders completed the first round. Methods: The study consisted of three components. (1) A systematic review of the literature to produce a list of outcomes reported in RCTs assessing the effectiveness of interventions for the treatment of pregnant women with PGDM. (2) A three‐round, online eDelphi survey to prioritise these outcomes by international stakeholders (including healthcare professionals, researchers and women with PGDM). (3) A consensus meeting where stakeholders from each group decided on the final COS. Main outcome measures: All outcomes were extracted from the literature. Results: We extracted 131 unique outcomes from 67 records meeting the full inclusion criteria. Of the 205 stakeholders who completed the first round, 174/205 (85%) and 165/174 (95%) completed rounds 2 and 3, respectively. Participants at the subsequent consensus meeting chose 19 outcomes for inclusion into the COS: trimester‐specific haemoglobin A1c, maternal weight gain during pregnancy, severe maternal hypoglycaemia, diabetic ketoacidosis, miscarriage, pregnancy‐induced hypertension, pre‐eclampsia, maternal death, birthweight, large for gestational age, small for gestational age, gestational age at birth, preterm birth, mode of birth, shoulder dystocia, neonatal hypoglycaemia, congenital malformations, stillbirth and neonatal death. Conclusions: This COS will enable better comparison between RCTs to produce robust evidence synthesis, improve trial reporting and optimise research efficiency in studies assessing treatment of pregnant women with PGDM. Tweetable abstract: 165 key stakeholders have developed #Treatment #CoreOutcomes in pregnant women with #diabetes existing before pregnancy. Tweetable abstract: 165 key stakeholders have developed #Treatment #CoreOutcomes in pregnant women with #diabetes existing before pregnancy.